Streptococcus mutans isolated from children with severe-early childhood caries form higher levels of persisters - Bottner, Aaron; He, Richard Y.; Sarbu, Andrea; Nainar, S.M. Hashim; Dufour, Delphine; Gong, Siew-Ging; Lévesque, Céline M. (Archives of oral biology, 2020)
•Dental caries is a chronic infectious disease.•Streptococcus mutans produces persisters, variants associated with infection chronicity.•S. mutans from severe caries children had more persisters compared to caries-free patients.•Ability of S. mutans to produce high levels of persisters may contribute to caries control. Dental caries is the most common chronic infectious disease in children. Streptococcus mutans, the main cariogenic bacterial species, produces persisters, nongrowing dormant variants of regular cells associated with chronicity of diseases. We hypothesized that the recurrent nature of caries, particularly within populations with high-caries risk, is due partly to specific phenotypic features of S. mutans such as its ability to form persisters. We aimed to investigate the genotypic and phenotypic differences between the S. mutans from children with severe early-childhood caries (S-ECC) and those without caries. S. mutans from plaque samples of caries-free (CF) and S-ECC children were tested for their ability to adapt to a lethal pH in an acid tolerance response assay. The persister levels of S. mutans isolates was quantified in both groups. S. mutanswas identified in all 23 S-ECC but only 6 of the 21 CF subjects. In most subjects, only one dominant S. mutans genotype was detected. No statistically significant differences in the mean survival percentage of S. mutans were observed between the two groups at a lethal pH of 3.5. However, the dominant genotype within a particular S-ECC subject exhibited a higher percentage of cell survival compared to those in the CF group. In S-ECC patients, S. mutans isolates displayed a ∼15-fold higher persistence phenotype than S. mutans isolates from CF patients. The ability of S. mutans to produce high levels of persisters may contribute to part of an individual’s ability to control caries disease activity and recurrent lesions.